The genetic architecture underlying the Caenorhabditis elegans response to grassland soil bacteria and its effects on fitness - Mony, Vinod Kurumathurmadam Namboothiripad (Kansas State University, 2013)
Soil nematode communities are important components of the micro fauna in grassland ecosystems and their interaction with soil microbes affects important ecological processes such as decomposition and nutrient recycling. To study genetic mechanisms underlying ecologically important traits involved in the response of nematode communities to soil microbes, we employed genomic tools available for the model nematode, Caenorhabditis elegans. Previous work identified 204 C. elegans genes that were differentially expressed in response to growth on four different bacteria: Bacillus megaterium, Pseudomonas sp., Micrococcus luteus and Escherichia coli. For many of the genes the degree of differential gene expression between two bacterial environments predicted the magnitude of the effect of the loss of gene function on life-history traits in those environments. Mutations can have differential effects on fitness in variable environments, which can influence their maintenance in a population. Our fitness assays revealed that bacterial environments had varying magnitude of stress, defined as an environment in which the wild-type has a relatively low fitness. We performed fitness assays as part of a comprehensive analysis of life history traits on thirty five strains that contained mutations in genes involved in the C. elegans response to E. coli, B. megaterium, Pseudomonas sp. We found that many of the mutations had conditionally beneficial effects and led to increased fitness when nematodes bearing them were exposed to stressful bacteria. We compared the relative fitness of strains bearing these mutations across bacterial environments and found that the deleterious effects of many mutations were alleviated in the presence of stressful bacteria. Although transcriptional profiling studies can identify genes that are differentially regulated in response to environmental stimuli, how the expressed genes provide functional specificity to a particular environment remains largely unknown. We focused on defense and metabolism genes involved in C. elegans-bacterial interactions and measured the survivorship of loss-of-function mutants in these genes exposed to different bacteria. We found that genes had both bacteria-specific and bacteria-shared responses. We then analyzed double mutant strains and found bacteria-specific genetic interaction effects. Plasticity in gene interactions and their environment-specific modulation have important implications for host phenotypic differentiation and adaptation to changing environments.
Keywords: Caenorhabditis elegans; Soil bacteria; Genetic architecture; Fitness; Biology (0306)